2022
DOI: 10.3389/fonc.2022.988800
|View full text |Cite
|
Sign up to set email alerts
|

A more effective CT synthesizer using transformers for cone-beam CT-guided adaptive radiotherapy

Abstract: PurposeThe challenge of cone-beam computed tomography (CBCT) is its low image quality, which limits its application for adaptive radiotherapy (ART). Despite recent substantial improvement in CBCT imaging using the deep learning method, the image quality still needs to be improved for effective ART application. Spurred by the advantages of transformers, which employs multi-head attention mechanisms to capture long-range contextual relations between image pixels, we proposed a novel transformer-based network (ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
(44 reference statements)
2
6
0
Order By: Relevance
“…Image quality and dose distribution were evaluated on the CBCT images corrected by HU-ED curves and sCT images generated by CycleGAN model, with RCT images as the ground truth.sCT images generated by the CycleGAN model successfully removed most scatter artifacts on the CBCT images. The image quality of SCT1 and SCT2 was visually comparable to the RCT, as Zhang et al 29 and Chen et al 30 reported. Moreover, the HU profile of sCT images in most regions, especially SCT2, was closer to that of RCT images.…”
Section: Discussionsupporting
confidence: 69%
“…Image quality and dose distribution were evaluated on the CBCT images corrected by HU-ED curves and sCT images generated by CycleGAN model, with RCT images as the ground truth.sCT images generated by the CycleGAN model successfully removed most scatter artifacts on the CBCT images. The image quality of SCT1 and SCT2 was visually comparable to the RCT, as Zhang et al 29 and Chen et al 30 reported. Moreover, the HU profile of sCT images in most regions, especially SCT2, was closer to that of RCT images.…”
Section: Discussionsupporting
confidence: 69%
“…Image quality and dose distribution were evaluated on the CBCT images corrected by HU-ED curves and sCT images generated by CycleGAN model, with RCT images as ground truth.As the result of side-by-side comparison shown, sCT images generated by CycleGAN model removed most scatter artifacts on the CBCT images. The image quality of SCT1 and SCT2 was visually comparable to the RCT, as Zhang et al 28 and Chen et al29 reported. Moreover, the HU pro le of STC images in different regions, especially SCT2, was closer to that of RCT images.…”
supporting
confidence: 71%
“…Finally, as the main deep learning baseline we implemented a 3D U-net for post-processing the FBP output and compared it to a two-dimensional post-processing baseline using a more recent Uformer model, 28 variants of which have lately been used for CBCT postprocessing in the literature. 33,34 We used U-net with 3…”
Section: Baseline Methodsmentioning
confidence: 99%
“…Finally, as the main deep learning baseline we implemented a 3D U‐net for post‐processing the FBP output and compared it to a two‐dimensional post‐processing baseline using a more recent Uformer model, 28 variants of which have lately been used for CBCT post‐processing in the literature 33,34 . We used U‐net with 3 downsampling layers, PReLU activations, valid convolutions and 64 base filters, similar to the original 3D U‐net, 27 but without Instance or Batch normalization layers.…”
Section: Methodsmentioning
confidence: 99%